AVALIAÇÃO MORFOLÓGICA DA MADEIRA DE ESPÉCIES FLORESTAIS - RIBEIRO, Eliane Alves; ARRUDA JUNIOR, Joilson Magalhães de; SILVA, Aline Cardoso; SIMPLICIO, Viviane dos Santos; COSTA, Emerson Belarmino; GOUVÊA, Adriana de Fátima Gomes (ANAIS DO ENIC, 2020)
-